A non-interactive lattice-based scheme supporting multiple blindness modes - Dinh Hai Le; Luong Vu Ngoc Bui (Institute of Advanced Engineering and Science, 2026)
This paper proposes a lattice based multi-mode blind signature framework that uniformly supports three operating modes: full blindness, partial blindness, and non-blindness. The design employs public matrices with trapdoors, combined with hash functions mapping into ℤ??, short preimage sampling mechanisms, and an identity encryption component to ensure fairness and enable traceability in case of misuse. Based on this construction, the user generates a blinded request, the signer produces a short response bound to the encrypted identity, and the user performs an unblinding step to obtain the final signature. The paper also presents the system model, research methodology, security claims, and parameter discussions in the post-quantum setting. The main properties analyzed include correctness, blindness, partial blindness, existential unforgeability, one more unforgeability, fairness, and traceability under the SIS and one more SIS assumptions. The results indicate that the proposed approach provides a flexible solution for applications requiring a balance between anonymity, accountability, and post-quantum security.